ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO PROFITABILITAS DAN RASIO AKTIVITAS PADA PT BATA TBK - Ratnaningsih Ratnaningsih; Tuti Alawiyah (Universitas Pakuan, 2018)
The purpose of this study was to analyze the financial performance of PT Bata Tbk by using profitability and activity ratios in the period of literature study. The research used the quantitative method and literature review. The research found that financial performances at PT Bata Tbk were less efficient. This could be seen in 2015s financial performance has increased while in 2014 and 2016 have decreased. PT Bata Tbk has failed in planning and developing its business strategy in an effort to obtain maximum profitability. Firm could not evaluate and measure performance standards that had been achieved on the basis of projected financial performance in the past, so that it could affect its customer loyalty and investor confidence levels. Meanwhile frequent fluctuations in the results which were achieved over a period of three years at PT Bata Tbk caused by unbalanced capital use, the management of its assets, and the imbalance between level of sales generated and suppressed cost. A slow inventory turnover rate and the low level of sales had leaded to lower profit level. Keywords: Financial Performance, Profitability Rati, Activity Ratio